A review on the application of Bills Of Quantities (BQ) in construction project procurement - Abdul Rashid, Khairuddin; Hasan, Sharina Farihah; Mohd Fauzi, Puteri Nur Farah Naadia; Aripin, Srazali; Ahmad Sarkawi, Azila (2016)
In Malaysia, Bills of Quantities (BQs) is widely used in project procurement. BQs, prepared by Quantity Surveyors, serves as one of the primary components of the tender and contract documents. However, in spite of its extensive use numerous questions were raised concerning the effectiveness of BQs in meeting the needs of project procurement. This paper provides a review of the BQs including its functions, types and critiques. The paper concludes with questions on the effectiveness of the BQs and whether the quantity surveying profession has moved forward or are old issues and problems remained unattended